Participation Of Women In Marketing: Economic Empowerment Of Farm Women - Thapa, Roahani (Journal of Agriculture and Environment, 2013)
Cash income in hand is a necessary condition for overall empowerment of women. For this purpose, women need to be involved in marketing. There are several projects implemented for the economic empowerment of women. However, the interrelatedness of involving women in marketing for overall empowerment of women has not been studied for policy purposes. Hence, this study has attempted to address this research gap. The objective of this study was to analyse the importance of involving women in marketing for their overall empowerment. In order to analyse the factors affecting decision making of the producers' group, a regression model was used. The findings of this study have clearly shown a linkage that when more women become the members of the producers group, then there is increased participation of women in the decision making process of the producers groups. When women are able to influence the decisions of the group, then they take-up market oriented production and start participating in the marketing activity. The study has concluded that women's involvement in marketing can be increased by increasing women's participation in producers' groups and promoting market oriented production. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 32-39 DOI: http://dx.doi.org/10.3126/aej.v13i0.7585